Pengembangan Trainer Kendali PID pada Sistem Fisik Elektrik Terintegrasi Aplikasi Pemograman Grafis - Rozani, Elvyra Jovanka; Sunarya, Adhitya Sumardi; Suryatini, Fitria (The Indonesian Journal of Computer Science, 2024)
Increased competencies in control systems are essential for the future of higher education in this field. Polytechnic Manufacturing Bandung aims to enhance the educational process by integrating theory and practice in automation and mechatronics, as reflected in their project-based learning curriculum. Previously, they created a trainer model for control systems that could only be read analogously with an oscilloscope, which was deemed insufficient for implementing control theory. Therefore, a physical trainer for electrical systems with an interface display and integrated PID controls is needed. Fifteen students evaluated this trainer using the Likert scale based on the EMPI approach, resulting in an average interface presentation score of 83.2%. This indicates that the physical trainer with PID controls and a graphical programming interface effectively represents control theory and supports the learning process.